Low-density lipoprotein receptor-related protein 1 as a potential therapeutic target in Alzheimer’s disease - Petralla, Sabrina; Panayotova, Maria; Franchina, Elisa; Fricker, Gert; Puris, Elena (Pharmaceutics, 2024)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease impacting the lives of millions of people worldwide. The formation of amyloid β (Aβ) plagues in the brain is the main pathological hallmark of AD. The Aβ deposits are formed due to the imbalance between the production and Aβ clearance in the brain and across the blood-brain barrier (BBB). In this respect, low-density lipoprotein receptor-related protein 1 (LRP1) plays a significant role by mediating both brain Aβ production and clearance. Due to its important role in AD pathogenesis, LRP1 is considered an attractive drug target for AD therapies. In the present review, we summarize the current knowledge about the role of LRP1 in AD pathogenesis as well as recent findings on changes in LRP1 expression and function in AD. Finally, we discuss the advances in utilizing LRP1 as a drug target for AD treatments as well as future perspectives on LRP1 research.